Efficacy of inoculation with isolates of Trichoderma spp. and Rhizobium leguminosarum in stimulating the growth of broad bean (Journal of the College of Basic Education, 2023)
The study was carried out to evaluate the effect of three isolates of Trichoderma spp. (T.26, T.h.In, and T.v.In) and isolates from the root-knot bacteria Rhizobium leguminosarum and the interaction between them in the emergence of seedlings and the growth of bean plants.The results showed that there was a significant superiority of the two treatments T.26 and Rhizobium leguminosarum, as it caused the highest significant increase in the index of seed germination and the percentage of germination over the rest of the treatments inoculated with biological agents, which in turn were significantly superior to the comparison treatment in both criteria.The results also showed that all treatments caused a significant increase in all studied plant growth parameters compared to the control treatment, which included the number of branches, the number of leaves, the plant height, the size of the root system, the number of root nodes, the number of flowers, the concentration of total chlorophyll in the leaves of the plant, the fresh weight of the group vegetative, dry weight of the vegetative total, fresh weight of the root total, dry weight of the root total with the superiority of the treatment with R. leguminosarum bacteria over the rest of the biological factors used in the study, as it recorded (6) branches, (34.5) leaves, (45) cm, (48) ml , (120) knots, (72) flowers, (33) mg total chlorophyll/gm dry tissue, (107) gm, (12.6) gm, (28) gm, and (8.2) gm, compared to the control treatment that recorded (3) (23) leaves, (29) cm, (30) ml, (70) knots, (60) flowers, (21) mg total chlorophyll/gm dry tissue, (44) gm, (7.2 (gm), (18) gm, (5.2) gm for growth standards above and respectively